Mexican agricultural frontier communities differ in forest dynamics with consequences for conservation and restoration. Issue 4 (26th April 2022) - Lohbeck, Madelon; DeVries, Ben; Bongers, Frans; Martinez‐Ramos, Miguel; Navarrete‐Segueda, Armando; Nicasio‐Arzeta, Sergio; Siebe, Christina; Pingarroni, Aline; Wies, Germán; Decuyper, Mathieu
Abstract: Forest regrowth is key to achieve restoration commitments, but a general lack of understanding when it occurs and how long secondary forests persist hampers effective upscaling. We quantified spatiotemporal forest dynamics in a recently colonized agricultural frontier in southern Mexico, and tested how temporal variation in climate, and cross‐community variation in land ownership, land quality and accessibility affect forest disturbance, regrowth and secondary forest persistence. We consistently found more forest loss than regrowth, resulting in a net decrease of 45% forest cover (1991–2016) in the study region. Secondary forest cover remained relatively constant while secondary forest persistence increased, suggesting that farmers are moving away from shifting cultivation. Temporal variation in disturbance was explained by annual variation in climatic variables and key policy and market interventions. We found large differences in forest characteristics across communities, and these were explained by differences in land ownership and soil quality. Forests were better conserved on communal land, while secondary forest was more persistent when farms were larger and soil quality is better. At the pixel‐level both old forest and secondary forests were better represented on low‐quality lands indicating agricultural concentration on productive land. Both old forest and secondary forest were less common close to the main road, where secondary forests were also less persistent. We demonstrate the suitability of timeseries analyses to quantify forest disturbance and regrowth and we analyse drivers across time and space. Communities differ in forest dynamics, indicating different possibilities, needs and interests. We warrant that stimulating private land ownership may cause remaining forest patches to be lost and that conservation initiatives should benefit the whole community. Forest regrowth competes with agricultural production and ensuring farmers have access to restoration benefits is key to restoration success. Abstract : We assess how differences in biophysical and social characteristics across time and space have shaped forest dynamics in agricultural frontier communities located in the Mesoamerican biodiversity hotspot in the humid tropics of Mexico. Our results show that forest conservation and restoration can be explained by a complex interplay of biophysical and social drivers across time and space. Communities differ in forest dynamics, indicating different possibilities, needs and interests. We warrant that further stimulating private land ownership may cause remaining forest patches to be lost and that conservation initiatives should benefit the whole community. In addition we show that forest regrowth and secondary forest persistence competes with agricultural production and that farmers will need to be incentivized to ensure restoration inside the agricultural frontier.